CORRELATION OF HIGH LDL WITH ANGIOGRAPHY FINDINGS IN PATIENTS WITH UNDERLYING CORONARY ARTERY DISEASE (The Research of Medical Science Review, 2025)
Introduction: Coronary artery disease (CAD) remains a leading cause of global morbidity and mortality, with elevated low-density lipoprotein (LDL) cholesterol being a well-established risk factor. However, the relationship between LDL levels and angiographic severity across different patient subgroups remains incompletely understood. This study aimed to determine the correlation of high LDL with angiography findings in patients with underlying coronary artery disease.Methodology: In this cross-sectional study, 462 patients with confirmed CAD underwent coronary angiography and LDL measurement. Angiographic severity was categorized as single-, double-, or triple-vessel disease. Spearman's correlation analysis evaluated LDL-angiography associations overall and across subgroups including gender, age, BMI, comorbidities, and CAD subtypes.Results: The overall population showed a significant positive correlation (r=0.579, p<0.001). Stronger associations emerged in males (r=0.629) versus females (r=0.512), smokers (r=0.689), and diabetics (r=0.614). Normal-weight patients (BMI<25) demonstrated higher correlations (r=0.605) than overweight/obese patients (r=0.561). Late presenters (≥12 hours post-symptom onset) had stronger correlations (r=0.607) than early presenters (r=0.547). Among CAD subtypes, stable angina (r=0.596) and NSTEMI (r=0.595) showed marginally stronger associations than STEMI (r=0.533).Conclusion: Our findings highlight the critical role of LDL cholesterol in the severity of CAD, while demonstrating notable differences among patient subgroups. The findings support tailored lipid management approaches, especially for high-risk populations such as smokers and diabetics, who exhibited the most significant connections with LDL-atherosclerosis